Prensa regional y local: el caso riojano durante la Restauración (1875-1902) - José Miguel Delgado Idarreta (Cahiers de Civilisation Espagnole Contemporaine)
Our main purpose is to analyse, from a general perspective, the existence of regional and local press and prove how said press is developed to such a degree in districts’ main cities, like in the capital of the then province of Logroño, now known as the Autonomous Community of La Rioja. We will examine its varied focuses, such as the political, official, religious, and educational perspectives, among others. One of the features of such press is its brevity in time: some newspapers were published for less than a year, some consisted of just a small number of initial issues, and some were only advertised for publication in another newspaper but were never actually published. Nevertheless, the phenomenon of La Rioja should also be mentioned; this newspaper was created in 1889 and it can still be read throughout the whole community of La Rioja.